The language picture of the world in the folk-lore (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The article deals with the question which concern the language picture of the world, the theme field “Animals”, which realizes in the Ukrainian and Russian lyric songs, is analyzed. The representation of the peoples’ world-views, the perception and comprehension of the environment and its reflection in the language is also presented here.
Keywords: the language picture of the world; comprehension of the world; the theme field